An orbital approach of electron transfer in multisite systems. Implications for carbon-rich spacers. (28th January 2015) - Launay, Jean-Pierre
Graphical abstract: Isolobal analogy between organometallic and organic sites; link with solid-state concepts. Electronic interaction through overlap of "magnetic-like" orbitals: decay of the HOMO of fragments with distance, case of even and odd bridges, and aromatic linkers. Electron–phonon interaction (Holstein and Peierls types). A three-state model for M–L–M systems. Abstract: A simple orbital approach is presented to treat electron transfer in mixed valence compounds with either organometallic (M(dppe)2 Cl, M(dppe)Cp ∗ ) or organic sites (triarylamine) and various bridges or spacers in particular carbon-rich ones. The orbital approach is based on the inspection of the HOMO of fragments constituting the complete system. The link is also made with solid-state concepts such as Holstein and Holstein-Peierls polarons. The HOMOs of different fragments are examined, in particular their decay along a conjugated chain starting from a donor group grafted at one extremity. Overlap considerations allow the qualitative prediction of the existence (or not) of an electronic interaction along a bridge. This approach is applied to a large variety of bridging systems with either an even or odd number of atoms: conjugated bridges, cross-conjugated systems, platinum bridges, aromatic bridges such as azulene or pyridine. The orbital approach allows also a discussion of the effect of oxidation on geometry changes (polaron formation), showing that the larger the fragment, the smaller the polaron energy. This is qualitatively applied to a series of mixed valence systems bridged by benzene, naphthalene or anthracene in the frame of a three-center model. ( ∗∗ ) in honor of Claude Lapinte, recognizing and appreciating a major actor of the chemistry developed in Rennes